Comparative evaluation of the extracellular production of a polyethylene terephthalate degrading cutinase by Corynebacterium glutamicum and leaky Escherichia coli in batch and fed-batch processes - Fritzsche, Stefanie; Hübner, Holger; Oldiges, Marco; Castiglione, Kathrin (Microbial Cell Factories, 2024)
BACKGROUND: With a growing global population, the generation of plastic waste and the depletion of fossil resources are major concerns that need to be addressed by developing sustainable and efficient plastic recycling methods. Biocatalytic recycling is emerging as a promising ecological alternative to conventional processes, particularly in the recycling of polyethylene terephthalate (PET). However, cost-effective production of the involved biocatalyst is essential for the transition of enzymatic PET recycling to a widely used industrial technology. Extracellular enzyme production using established organisms such as Escherichia coli or Corynebacterium glutamicum offers a promising way to reduce downstream processing costs. RESULTS: In this study, we compared extracellular recombinant protein production by classical secretion in C. glutamicum and by membrane leakage in E. coli. A superior extracellular release of the cutinase ICCGDAQI was observed with E. coli in batch and fed-batch processes on a litre-scale. This phenomenon in E. coli, in the absence of a signal peptide, might be associated with membrane-destabilizing catalytic properties of the expressed cutinase. Optimisations regarding induction, expression temperature and duration as well as carbon source significantly enhanced extracellular cutinase activity. In particular, in fed-batch cultivation of E. coli at 30 °C with lactose as carbon source and inducer, a remarkable extracellular activity (137 U mL-1) and cutinase titre (660 mg L-1) were achieved after 48 h. Literature values obtained with other secretory organisms, such as Bacillus subtilis or Komagataella phaffii were clearly outperformed. The extracellular ICCGDAQI produced showed high efficacy in the hydrolysis of PET textile fibres, either chromatographically purified or unpurified as culture supernatant. In less than 18 h, 10 g L-1 substrate was hydrolysed using supernatant containing 3 mg cutinase ICCGDAQI at 70 °C, pH 9 with terephthalic acid yields of up to 97.8%. CONCLUSION: Extracellular production can reduce the cost of recombinant proteins by simplifying downstream processing. In the case of the PET-hydrolysing cutinase ICCGDAQI, it was even possible to avoid chromatographic purification and still achieve efficient PET hydrolysis. With such production approaches and their further optimisation, enzymatic recycling of PET can contribute to a more efficient and environmentally friendly solution to the industrial recycling of plastics in the future.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Autoinduction; Bioreactor; Cutinase; Enzymatic depolymerization; Extracellular; Lactose feed; Polyethylene terephthalate; Recombinant protein expression; Secretion